Microfibril Angles and Crystalline Properties of Reaction Woods in Agathis and Sumatran Pine Woods - Purusatama, Byantara Darsan; Febrianto, Fauzi; Hidayat, Wahyu; Kim, Nam Hun (Jurnal Sylva Lestari, 2024)
The microfibril angles (MFAs), relative crystallinity index (RC), and crystallite width (CrW) of compression wood (CPW), lateral wood (LTW), and opposite wood (OPW) in Agathis (Agathis loranthifolia) and Sumatran Pine (Pinus merkusii) stem wood were observed and compared to obtain valuable information on wood quality for effective utilization. The iodine staining method and optical microscopy were applied to measure the MFA in the tangential section. RC and CrW were analyzed with an X-ray diffraction technique. CPW had the largest MFA and the smallest RC in both species. In Agathis, LTW and OPW had comparable MFA, RC, and CrW, whereas the CrW of CPW was the smallest. In Sumatran pine, there was a significant difference in MFA and RC between LTW and OPW. CPW, LTW, and OPW showed comparable CrW. The MFA decreased and RC increased from near the pith to bark in both species. The CrW increased from near the pith to the bark of Sumatran pine, whereas it was constant in Agathis. In conclusion, MFA and RC could be used to identify CPW, LTW, and OPW in both species. There were distinctive MFA and RC properties between reaction wood in both species. Keywords: Agathis loranthifolia, crystalline properties, microfibril angles, Pinus merkusii, reaction wood